DAMPAK HUKUM KREDITOR ATAS PEMBATALAN HAK TANGGUNGAN BERDASARKAN PUTUSAN PENGADILAN - Zaidan Yusuf Kinayungan; Harjono Harjono (Verstek, 2023)
This article analyzes the legal impact on creditors of a mortgage rights that is cancelled by law based on a court decision. This article aims to find out how the legal consequences of amortgage rights that is cancelled by law based on a court decision. The research method used in this article is a normative legal research method. This research is prescriptive and applied. The technique of collecting legal material used in this research is a literature study with primary and secondary legal materials. Based on the results of the research, it can be concluded that the legal impact of creditors on the cancellation of mortgage rights based on court decisions is the loss of the creditor's position as a separatist creditor with the right to parate execute on the basis of the executorial title to become a concurrent creditor who has the same position as other creditors without mortgage rights.Keywords: Cancellation of Mortgage Rights, Legal Impact, Creditor’s Position